Day 3 Wed, November 13, 2019 2019
DOI: 10.2118/197515-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Ethoxylated Amine Surfactant for CO2-Foam Stability at High Salinity Conditions

Abstract: CO2 flooding is well-known to be an effective EOR method and has been successfully implemented around the world. In heterogeneous formations, CO2 foam has been utilized to achieve conformance and mobility control. However, the foam performance degrades significantly at high saline environments. Ethoxylated amines have been reported to be successful in high pressure-high temperature (HPHT) conditions. This paper investigates the results obtained from a study of the foamability and foam stability at varying sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Noor et al reported optimal foam stability at a 2 wt % NaCl BOR of foaming solution . In another study by Le et al, they reported the foamability and foam stability of a surfactant at different salinities . Similarly, Somoza et al identified a constant optimal surfactant concentration of 0.25 wt % for foam stability across a salinity range of 0 to 15 wt % NaCl .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noor et al reported optimal foam stability at a 2 wt % NaCl BOR of foaming solution . In another study by Le et al, they reported the foamability and foam stability of a surfactant at different salinities . Similarly, Somoza et al identified a constant optimal surfactant concentration of 0.25 wt % for foam stability across a salinity range of 0 to 15 wt % NaCl .…”
Section: Resultsmentioning
confidence: 99%
“…80 In another study by Le et al, they reported the foamability and foam stability of a surfactant at different salinities. 81 Similarly, Somoza et al identified a constant optimal surfactant concentration of 0.25 wt % for foam stability across a salinity range of 0 to 15 wt % NaCl. 22 In the present study, the effects of BOR were explored in an emulsion solution.…”
Section: Half-life Time Of Foammentioning
confidence: 98%
“…Moreover, it is preferential to measure the CO 2 -soluble surfactant distribution among three phases (aqueous/gaseous/oleic) to indicate the potential adverse emulsion generation 78 or surfactant loss. 79 When further zooming out to the core or even the macroscopic scale, it has been showed that foam stability and foamability are highly relevant to surfactant properties reflected through multiple aspects, including surfactant concentration, 80 temperature, 81 pressure, 82 salinity, 83 pH, and injection velocities. 62 The semi-quantitative studies here reveal that it would not be straightforward to achieve the eventual results, since the structure-related properties of those CO 2 -soluble surfactants could impose opposite impacts on the foam performances.…”
Section: Further Discussionmentioning
confidence: 99%
“…Moreover, it is preferential to measure the CO 2 -soluble surfactant distribution among three phases (aqueous/gaseous/oleic) to indicate the potential adverse emulsion generation or surfactant loss . When further zooming out to the core or even the macroscopic scale, it has been showed that foam stability and foamability are highly relevant to surfactant properties reflected through multiple aspects, including surfactant concentration, temperature, pressure, salinity, pH, and injection velocities …”
Section: Further Discussionmentioning
confidence: 99%